Reflections of a Zen Buddhist nun - Kim, Ir-yŏp (Korean classics library. Philosophy and religion, 2014)
Cover -- Contents -- Acknowledgments -- Translator's Introduction: Kim Iryŏp, Her Life and Thought -- Part One -- Chapter 1 Preface -- Chapter 2 Life -- Chapter 3 Buddhism and Culture -- Chapter 4 In Memory of the Great Master Man'gong on the Fifteenth Anniversary of His Death -- Chapter 5 On New Year's Day of the Twenty-Fifth Year after Joining the Monastery -- Chapter 6 A Proposal to the World Fellowship of Buddhists Conference -- Chapter 7 Why Has Buddhism Launched a Purification Movement? -- Chapter 8 Is the Mind One or Two? To Mr. C., Who Has Recently Converted to Catholicism -- Chapter 9 What Is Faith? Contemplation upon Reading a Letter from My Friend M. -- Chapter 10 The Path to No-Mind: A Letter to Mr. R. -- Chapter 11 Having Burned Away My Youth: A Letter to Mr. B. -- Chapter 12 With a Returned Gift in My Hand -- Chapter 13 Having Prepared a Clean Copy of My Master's Manuscript (by Yi Wŏlsong) -- Part Two -- Chapter 14 Return to Emptiness -- Chapter 15 Meditation and the Attainment of the Mind -- Chapter 16 Prayer and Chanting -- Chapter 17 Path to Eternity: A Message to Journalists -- Notes -- Character Glossary -- Bibliography -- Index.